Predictors of depression and anxiety symptom trajectories in the 24 months following diagnosis of breast or gynaecologic cancer. (April 2016) - Stafford, Lesley; Komiti, Angela; Bousman, Chad; Judd, Fiona; Gibson, Penny; Mann, G. Bruce; Quinn, Michael
Abstract: Objective: To identify predictors of anxiety and depression symptom trajectories, as distinct from general distress, in the 96 weeks following diagnosis of breast or gynaecologic cancer. Methods: Participants completed the Hospital Anxiety and Depression Scale anxiety subscale (HADS-A) and Centre for Epidemiological Studies Depression Scale (CES-D) at diagnosis and at 8-weekly intervals for 96 weeks. Linear mixed models were used to determine the effects of age, relationship status, tumour stream, cancer stage, living situation, residential area, educational status, current and previous anxiety/depression treatment and neuroticism on symptom trajectories. Results: Participants were 264 women with a mean (SD) age of 54 (12) years. Compared to non-treatment-receiving counterparts, women who received anxiety/depression treatment in the past had depression and anxiety symptom severity scores that were 4.58 and 1.24 higher, respectively. Women receiving such treatment at cancer diagnosis had depression and anxiety scores that were 4.34 and 2.35 points higher, respectively, than their counterparts. Compared to women with the lowest neuroticism scores, women with the highest scores scored 8.48 and 3.82 higher on the CES-D and HADS-A, respectively. Depressive severity remained stable but anxiety severity decreased as a function of neuroticism. Conclusions: In settings with limited resources, women with high neuroticism or a depression/anxiety treatment history should be the initial target of psychological screening. Identification of women with these characteristics at the earliest point of entry into the oncology service followed by heightened surveillance and/or referral to psychosocial services may be useful to prevent chronic psychological morbidity. Highlights: We identify characteristics predictive of psychological symptom severity over 2 years. Women with previous anxiety/depression treatment had worse depression and anxiety profiles. Women with high neuroticism had worse anxiety and depression profiles. Anxiety severity decreased as a function of neuroticism. Women with these characteristics should be the initial target of screening initiatives.